European Identity – Top Down or Bottom Up? (KULT_online, 2011)
This essay collection approaches the issue of European identity, which has been so controversially discussed and highly politicised in recent years, from a determinedly interdisciplinary perspective. The theoretical-programmatic as well as empirical contributions by renowned political scientists, historians, sociologists, and anthropologists undertake in particular the task of finding a middle ground between the top-down and bottom-up approaches which are prevalent, but often treated separately, within the field of European Studies. In most essays, however, European identity is rather too hastily equated with EU identity, and a view towards the process-related, long-term perspective of European identity is impeded by insufficient historicisation.